1995
DOI: 10.1007/bf00941844
|View full text |Cite
|
Sign up to set email alerts
|

Three-phase bone scintigraphy pattern of loosening in uncemented hip prostheses

Abstract: The three-phase bone scintigraphy pattern of loosening in uncemented hip prostheses (UHPs) has not previously been elucidated. We evaluated 28 patients with complicated UHPs who had undergone total hip arthroplasty a very long time previously (range 3-20 years, mean 8.4). All the patients were surgically reviewed: 26 UHPs were found to be loosened and two infected. Nine asymptomatic UHPs were taken as controls. The dynamic phase was invariably negative in both loosened and asymptomatic UHPs while markedly posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…2 In this setting, the sensitivity was reported as 94% and specificity was 95%, when positive results during the blood flow, blood pool and late phase were interpreted as indicative of infection. 2 Rubello et al 10 reported 100% sensitivity and specificity for triple-phase bone scintigraphy in two patients with prosthetic implants, and Reinartz et al 11 found that the sensitivity and specificity of triple-phase bone scintigraphy was 68% and 76%, respectively, in a series of eight patients with peri-prosthetic infection. However, in these reports, the authors defined infection as showing positive results for the blood pool and late phases only.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 In this setting, the sensitivity was reported as 94% and specificity was 95%, when positive results during the blood flow, blood pool and late phase were interpreted as indicative of infection. 2 Rubello et al 10 reported 100% sensitivity and specificity for triple-phase bone scintigraphy in two patients with prosthetic implants, and Reinartz et al 11 found that the sensitivity and specificity of triple-phase bone scintigraphy was 68% and 76%, respectively, in a series of eight patients with peri-prosthetic infection. However, in these reports, the authors defined infection as showing positive results for the blood pool and late phases only.…”
Section: Discussionmentioning
confidence: 99%
“…Positron-emission tomography has been used for the differential diagnosis of a painful THR. 10 Although it has proven useful in diagnosing malignant tumours, it is not thought to be sensitive enough to distinguish between infected and non-infected implants. 13,14 Furthermore, it is expensive and remains limited to a few institutions, whereas triple-phase bone scintigraphy is widely available and inexpensive.…”
Section: Discussionmentioning
confidence: 99%
“…Acetabular radiolucent lines and osteolysis were measured using the zones described by DeLee and Charnley [7]. With this method, an increased uptake in blood pool and bone phase suggests possible loosening of the cup [9]. Heterotopic ossification was assessed using the classification of Brooker et al [8].…”
Section: Methodsmentioning
confidence: 99%
“…[ 4 ] However these findings in combination with the bone scan findings, provided enough suspicion of a pathology sinister enough to refer the patient for surgical hardware revision with potential biopsy. [ 5 6 ]…”
Section: Case Reportmentioning
confidence: 99%